2023
DOI: 10.3390/foods12203843
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gluten Composition in Low-Allergy O-Free Wheat Flour on Cookie-Making Performance Compared with Flours with Different Gluten Strengths

Nayeon Baek,
Yujin Moon,
Jeongeon Kim
et al.

Abstract: The increasing demand for allergen-free and reduced-allergen foods has led to an investigation into the potential use of O-free wheat, a low-allergy wheat cultivar, in cookie production. This study focused on assessing the gluten composition of O-free flour and comparing its suitability for cookie making in comparison to flours with varying gluten strengths. Several analyses were conducted, including gluten composition, solvent retention capacity (SRC), thermal and pasting properties, dough-mixing characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…It should be noted that, compared to bread, gluten plays a minor role in biscuits, with its development generally being regarded as undesirable as it can create problems (excessive shrinkage or distortion, thickness reduction, and checking), which causes biscuits to break or crack after baking [ 14 , 15 ]. However, the role of gluten quality and composition is critical to the characteristics of cookie dough [ 16 ]. Furthermore, it has been found that adding legume flour to biscuits boosts protein content correspondingly while decreasing dough spread.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that, compared to bread, gluten plays a minor role in biscuits, with its development generally being regarded as undesirable as it can create problems (excessive shrinkage or distortion, thickness reduction, and checking), which causes biscuits to break or crack after baking [ 14 , 15 ]. However, the role of gluten quality and composition is critical to the characteristics of cookie dough [ 16 ]. Furthermore, it has been found that adding legume flour to biscuits boosts protein content correspondingly while decreasing dough spread.…”
Section: Introductionmentioning
confidence: 99%